No I won’t, but yes we will: driving sustainability-related donations through social identity effects - Champniss, Guy; Wilson, Hugh; Macdonald, Emma K.; Dimitriu, Radu (Elsevier, 2016)
Shifting consumers towards sustainable behaviours is difficult, with an attitude–behaviour gap persistently reported. This study proposes a route towards sustainable behaviours that does not depend on individual attitudes or values: social identity forces within novel online brand-convened consumer groups. A field experiment using a fictitious fruit drink brand demonstrates that by assembling an online consumer group and providing it with sustainability objectives, consumers will engage in a sustainability-aligned behaviour, namely donating to social or environmental charities at the request of the firm, irrespective of their individual attitudes. Furthermore, this behaviour is accompanied by an improvement in brand attachment. As these effects are found within a newly-formed online group, practitioners may be able to achieve sustainability objectives through this mechanism even in the absence of well-established brand communities. The study contributes to social identity literature by demonstrating the impact of group identity effects in a consumer context, and by showing a mechanism by which the negative side of group identity – out-group derogation – can be avoided.
Keywords: Social identity theory; Social categorisation theory; Sustainability; Consumer behaviour; Brand attachment; Social media